Socialization and Operational Training of Garbage Burners as a Solution to Reducing Piled Volume at Tegal Regency Garbage Disposal Sites - Farid, Ahmad; Renggani W, Galuh; Wibowo, Hadi; Hidayat, Royan (Universitas Pancasakti Tegal, 2022)
In the case of Tegal Regency, the limitation of waste disposal at the TPA is due to the process of revamping it, resulting in several villages making efforts to deal with waste problems independently by managing them under village-owned enterprises through the process of collecting waste from residents' homes, then sorting, processing waste, recycling, and burning when it can no longer be processed. The manual combustion process by burning directly on the trash cannot produce complete combustion because the waste condition is usually wet. The various types result in the garbage being unable to burn evenly and running out, especially during the rainy season. The amount of unburned waste will increase and pile up. Besides that, the garbage disposal location on the side of the road can disturb road users because of the foul smell and, of course, the unhealthy air. The method used in this community service activity is to socialize on the first day about the impact of the waste problem, information about several examples of waste incinerators, waste management and the application of the waste recycling process. The next day was a simulation of burning waste using a waste burner based on used oil and water. The operational strategy of burning is the main activity in community service. The end result of this training is that all waste managers can operate the tools and hope that the existing tools can be donated as examples for manufacturing and application at waste disposal sites.